上顎に生じた象牙質形成性幻影細胞腫の1例 - 伊藤, 弘人; 神部, 芳則; 森, 良之; 松本, 直行; 小宮山, 一雄; 佐瀬, 美和子 (日本口腔外科学会雑誌, 2015)
Dentinogenic ghost cell tumor (DGCT) is a rare tumor that often shows an aggressive growth pattern. DGCT has a high recurrence rate after tumor resection. We describe a case of DGCT of the maxilla that recurred after local resection. A 65-year-old man was referred to our hospital because of painful swelling of the left side of the maxilla. Computed tomography (CT) showed a bone defect in the left upper jaw and a mass lesion with invasion of the surrounding soft tissue. A calcifying cystic odontogenic tumor (CCOT) was diagnosed on biopsy, and the tumor was resected with the patient under general anesthesia. The histopathological diagnosis was DGCT. Ten months postoperatively, CT showed tumor recurrence in the same area, associated with a highly invasive pattern of growth. Partial resection of the maxilla was performed. The postoperative course was uneventful, and there was no sign of recurrence during 12 months of follow-up.